2005
DOI: 10.1590/s0037-86822005000400001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anti-hepatits A antibodies in children of different socioeconomic conditions in Vila Velha, ES

Abstract: This report describes the prevalence of anti-HAV antibodies in children from elementary school in the Municipality of Vila

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 21 publications
3
13
1
6
Order By: Relevance
“…In semiarid northeastern locations, especially smaller towns such as the village of Cavunge, environmental pollution is probably the main determinant of several fecal-oral transmission diseases. In this context, this population is different from other moredeveloped regions of the country, where HAV infection is observed in older individuals [23].…”
Section: Discussionmentioning
confidence: 77%
“…In semiarid northeastern locations, especially smaller towns such as the village of Cavunge, environmental pollution is probably the main determinant of several fecal-oral transmission diseases. In this context, this population is different from other moredeveloped regions of the country, where HAV infection is observed in older individuals [23].…”
Section: Discussionmentioning
confidence: 77%
“…3 In Brazil, a multicenter study found intermediate endemicities in the Southern and Southeastern regions (anti-HAV prevalence rates of 55.7%) and in the Northeastern region (76.5%) and high endemicity in the Northern region (92.8%). 4 In other studies performed in cities of Southeastern Brazil, the following seroprevalences of anti-HAV were observed: 32.1% in individuals aged between 1 and 23 years, in Rio de Janeiro, RJ; 5 38.6% in children aged between 4 and 14 years, in Vila Velha, ES; 6 and 54.2% in adolescents aged between 10.4 and 19.9 years, in São Paulo, SP. 7 Lower exposure to HAV in childhood causes adults to be vulnerable to such infection, when the disease has a higher morbidity.…”
Section: Introductionmentioning
confidence: 78%
“…Other studies performed in the Southeastern region of Brazil have shown lower seroprevalence rates, especially when groups with higher socioeconomic status were analyzed 10,20,23 . By contrast, studies performed in the Northern region showed a 86.4% seroprevalence of hepatitis A among children from two to nine years (n = 487) 3 , and 90.9% in riverine children from 0 to 10 years old (n = 22) 16 .…”
Section: Discussionmentioning
confidence: 93%
“…Hepatitis A seroprevalence studies in Brazil have shown different rates according to the period when sera were collected, but also to the socioeconomic background of the communities analyzed 3,8,10,11,16,18,20,23 .…”
Section: Introductionmentioning
confidence: 99%